COMPARISON OF MACHINE LEARNING ALGORITHMS FOR PREDICTING MORTALITY FROM COVID-19 VIRUS - Doroshenko, Iryna; Knihnitska, Tatiana; Deretorska, Tetiana (SWorldJournal, 2022)
The article compares the effectiveness of Machine Learning Algorithms on the example of Covid-19 distribution data. The following Machine Learning algorithms are considered: Logistic Regression, Support Vector Machine, Random Forest, K-Means. The accuracy of the constructed models was used to compare the Algorithms. All statistical studies were conducted in the R Programming language
ПОРІВНЯННЯ АЛГОРИТМІВМАШИННОГО НАВЧАННЯ ДЛЯПРОГНОЗУВАННЯ СМЕРТНОСТІ ВІД ВІРУСУ COVID-19
Keywords: Machine Learning; Support Vector Machine; Random Forest; Logistic Regression